A cross-sectional survey of knowledge, attitude, and willingness to engage in spontaneous reporting of adverse drug reactions by Korean consumers - Seungyeon Kim; Yun Mi Yu; Myoungsoon You; Kyeong Hye Jeong; Euni Lee (BMC, 2020)
Abstract Background Spontaneous reporting (SR) of adverse drug reactions (ADRs) from patients can be considered as a valuable activity providing both objective and subjective data. However, improving the rate of under-reporting has been a major challenge to ensure successful operation of the SR system. This study aimed to assess knowledge, attitude, and intent to report ADRs and explore the factors contributing to consumers' reporting intent in South Korea. Methods Self-administered questionnaire was collected from a sex-, age-, and regionally stratified nationwide convenience sample of consumers using a commercial panel in December 2018. Univariate and multivariate logistic regression analyses were used to explore the factors contributing to the intent to report ADRs by consumers. Results A total of 1000 respondents were enrolled in the survey; 50.9% were males and the mean age was 44.4 (standard deviation, 13.3) years. While less than 15% of the respondents were aware of the SR system and even fewer (3.4%) had actual experience of SR, however, 59.2% expressed their intent to report ADRs. The positive attitude (adjusted odds ratio [aOR] 3.972, p < 0.001), awareness of the SR system (aOR 2.102, p < 0.01), self-efficacy for SR (aOR 1.956, p < 0.001), and experiences related to ADR counselling with healthcare professionals (OR 2.318, p < 0.001) are the significant factors contributing to reporting intent. Conclusions Findings of this study highlight the need for increasing the awareness of the SR system among consumers and empowering them to report ADRs by themselves, which would ultimately improve the drug-safety environment.